Занимательный компьютер: Кн. для детей, учителей и родителей / Симонович С.В., Евсеев Г.А. - Симонович С. В. (АСТ-Пресс Книга, 2002)
Экземпляры: Ф. 2 (20210708) / Инвентарный номер: 37346 / Авт.знак: С37 / ГРНТИ: 20 / ББК: 32.973